Effect of Different Nutrition to Tissues Culture of Banana Propagation : https://doi.org/10.69692/SUJMRD1004172 - PHOUTHAXAY, Phonesavanh; ANOUSACK, Phonekeo; BOUPHAKEO, Pharsern (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The experiment of propagation of banana with tissues culture was aimed to find the suitable food formula, which can stimulate the banana to grow well, especially the number of shoots and the number of roots, using a complete randomized design (CRD) consisting of 4 replicates and 8 treatments such T1 = MS + 0 mg/1 BAP +0 mg/1 NAA, T2 = MS + 1mg/l BAP +0 mg/1 NAA, T3= MS + 3 mg/1 BAP +0 mg/1 NAA, T4 = MS + 5 mg/1 BAP +0 mg/1 NAA, T5 = MS + 0 mg/1 BAP + 0.5mg/1 NAA, T6 = MS + 1 mg/1 BAP + 0.5 mg/1 NAA, T7 = MS + 3 mg/1 BAP +0.5 mg/1 NAA, T8 = MS + 5 mg/1 BAP + 0.5 mg/1 NAA. Throughout the experiment period, data was collected on the growth of each treatment every 7 days until 28 days with an average total of 4 weeks. From the results of collecting data in each treatment, it shows that: the formula that makes the banana grow better is T7, especially during the 28 day, the average shoot percentage is 100%, the average number of shoots is 8.73 cm, the average rooting percentage is 100%, the average number of roots is 4.5 roots, and the root length is 6.17cm was compared to other treatment was significance at 95%. So it can be said that the most suitable formula for propagating of banana by tissues culture was the T7 and can be used in the future for further experiments.